Emprego de matriz óssea orgânica bovina e hidroxiapatita no reparo de defeito induzido em crânio de ratos - Braz, Fabiano [UNESP]; Raha, Sheila Canevese [UNESP]; Rocha, Noeme De Sousa [UNESP]; Taga, Eulázio; Biasi, Fernando De [UNESP] (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2003)
PURPOSE: The aim of this study was to evaluate the biological response and inductor effect of the hydroxyapatite combined with bovine organic bone matrix. METHODS: Skull defects were induced on 20 male albino rats, with initial body weight between 300 and 350 grams. The animals were divided into two groups. In group I the defect was filled with hydroxyapatite combined with bovine organic bone matrix, and in group II no product was used. Five animals of each group were euthanised 30 and 60 days after the surgery for histopathological evaluation. RESULTS: Bone reabsorption was more evident in the group II at 30 days post surgery. There was no difference on presence of cartilage between moments in the same group. Statistical difference was observed between group I and II at 30 days after the surgery. At day 60 post surgery, animals from group I showed a higher quantity of osteoblasts and cartilage compare to group II. CONCLUSION: It was possible to conclude that hydroxyapatite combined with bovine organic bone matrix does not produce adverse reaction and induce bone repair.

OBJETIVO: Avaliar a resposta biológica e poder indutor da combinação matriz óssea orgânica bovina e hidroxiapatita. MÉTODOS: Foram produzidos defeitos ósseos em crânios de 20 ratos, Wistar, machos, com peso inicial médio entre 300 e 350 gramas, divididos eqüitativamente em dois grupos. No grupo I o defeito foi preenchido com uma associação de matriz óssea orgânica bovina e hidroxiapatita, ao passo que no grupo II considerado controle, nada foi empregado. Para o estudo histológico foram submetidos à eutanásia, cinco animais de cada grupo, aos 30 e 60 dias de pós-operatório. RESULTADOS: Com 30 dias de pós-operatório a reabsorção óssea foi maior no grupo II. A presença de cartilagem não diferiu entre os momentos de um mesmo grupo, porém houve diferença estatística entre os grupos I e II aos 30 dias, sendo maior no grupo I. Aos 60 dias de pós-operatório, o grupo I apresentava uma maior quantidade de osteoblastos e presença de osso comparativamente ao grupo II. CONCLUSÃO: A combinação matriz óssea orgânica bovina e hidroxiapatita não causa reações adversas e favorece a reparação óssea.
Use of bovine organic bone matrix and hydroxyapatite in repair of skull defects in rats
Keywords: Hydroxyapatite; Bovine organic bone matrix; Rats; Bone defect; Hidroxiapatita; Matriz óssea orgânica bovina; Ratos; Defeito ósseo